Recursos digitales como apoyo al proceso educativo de estudiantes con problemas de aprendizaje en la Unidad Educativa Particular Ateneo de la Ciudad de Loja año lectivo 2022-2023. - Jiménez Alberca, Yolanda Elizabeth (2023)
The present research work digital resources as support to the educational process in students with learning disabilities had as its general objective to analyze digital educational resources that support the educational process in students with learning disabilities in the Ateneo Educational Particular Unit in the city of Loja. To develop this research the methodology used was the deductive method with a quantitative approach and a descriptive type study was conducted, the population with which we worked were 12 teachers of the institution, and conversations were held with the staff of the Department of Student Counseling (DECE) and it was realized the observation sheets with those are registered the follow-up to each student with learning disabilities is recorded, likewise a research instrument was applied to determine the use of digital resources to students with learning disabilities in the teaching-learning process. It was obtained as a result that the web provides several options of easily accessible digital resources; however, teachers have stated that they do not use these resources to support classroom teaching, this way is noticed the lack of integration of technology in the training process. This allows us to deduce that the educational institution should include in the Institutional Educational Project (PEI) the training of teachers and in this way be able to provide the necessary support in teaching students with learning disabilities. Keywords: DECE, Learning disabilities, Technology, Digital resources.